African bat species distribution models and gridded IUCN expert maps: differences and implications for macroecological analyses - data in map form - K Matthias B Herkt; Jakob Fahr (PANGAEA, 2017)
Content: (a) 183 individual species distribution estimates (one set consists of MaxEnt species distribution models, the other set of rasterized IUCN expert maps). (b) pictures of the 183 maps of pairwise agreement (c) the two species richness maps obtained when stacking the aforementioned binary distribution maps. (d) a map showing the geographic distribution of sampling effort concerning African bats until ~2013, quantified using a kernel density estimate around documented presence localities. (e) maps of three environmental correlates of macroecological interest (annual net primary productivity representing the productivity hypothesis, standard deviation of annual actual evapotranspiration representing the seasonality hypothesis and diversity of elevation-refined land cover types representing the heterogeneity hypothesis). Note: all maps are in GeoTIFF format and provided at 200x200 km^2 spatial resolution, the grain at which we performed the analysis. Note that all SDMs were originally produced at 1 km2 grain and coarsened for the purpose of this analysis. Please consult our two papers listed below for more details.
In supplement to: Herkt, K Matthias B; Skidmore, Andrew K; Fahr, Jakob (2017): Macroecological conclusions based on IUCN expert maps: a call for caution. Global Ecology and Biogeography, 26(8), 930-941, https://doi.org/10.1111/geb.12601